2006
DOI: 10.1080/00016480510012363
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the cause of acute sensorineural hearing loss between Ménière's disease and sudden deafness

Abstract: Significant differences were found between MD and sudden deafness in terms of the recruitment phenomenon (86% and 21% of cases, respectively) and abnormal VEMP responses (71% and 21% of cases, respectively). However, the diseases did not differ significantly in terms of abnormal DPOAEs or caloric test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
0
18
2
Order By: Relevance
“…Opposed to a previous report, this study showed that both recruitment phenomenon and the cVEMP test failed to differentiate between contralateral RSD and contralateral DEH at the second episode. The reason is probably because the first episode (mainly SD) may cause various involvement severities in one or both ears.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Opposed to a previous report, this study showed that both recruitment phenomenon and the cVEMP test failed to differentiate between contralateral RSD and contralateral DEH at the second episode. The reason is probably because the first episode (mainly SD) may cause various involvement severities in one or both ears.…”
Section: Discussioncontrasting
confidence: 99%
“…Of them, differentiating between SD and EH is important, because both diseases have a significant overlap in symptoms, and treatment modalities differ. A previous report indicated that both the cervical vestibular‐evoked myogenic potential (cVEMP) test and recruitment phenomenon may act as a diagnostic algorithm to differentiate acute hearing loss between SD and EH . Despite immediate treatment, some SD patients had severe to profound hearing loss remaining in the first ear.…”
mentioning
confidence: 99%
“…However, only a small number of recent studies have included VEMP testing in the evaluation of subjects suffering sudden hearing loss, and have reported contradictory results: the incidence of VEMP abnormality has ranged from 0 to 77 per cent in different patient series. [15][16][17][18][19][20] Abnormal VEMP findings in patients with sudden hearing loss have been attributed either to a sacculo-labyrinthine lesion 16,18 or to brainstem hypoperfusion. 17 In the present study of over 100 sudden hearing loss patients, a considerable percentage had abnormal VEMP and/or caloric (with ENG) test results (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Recently, the new diagnostic method of vestibular evoked myogenic potential (VEMP) testing has been included in the evaluation of patients suffering idiopathic sudden hearing loss. [15][16][17][18][19][20] A recent study indicated that the results of audiovestibular function testing, including VEMP testing, correlated with the hearing outcome in cases of severe and profound sudden hearing loss. 19 To date, the involvement of the otolithic organs in idiopathic sensorineural hearing loss remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…dehydration for hydrops, yet hydration (or transfusion for hematological patients) for improving cochlear perfusion in sudden sensorineural hearing loss [19,20]. Fortunately, by way of stapedial reflex test, recruitment phenomenon can be used to differentiate between endolymphatic hydrops and sudden sensorineural hearing loss.…”
Section: Clinical Relevancementioning
confidence: 99%